Outsiders na EJA: gênero e identidade das mulheres nas pesquisas em educação de Minas Gerais - Nascimento, Mariana Teodoro (2024)
This research aimed to understand how women in Educação de Jovens e Adultos (EJA) (Adult and Youth Education) have been interpreted in studies conducted in the last 5 years in postgraduate programs in education in the state of Minas Gerais, Brazil. To achieve this, research available in the databases of universities with PPGEs was selected. Out of 2923 research works, including theses and dissertations, only 131 focused on AYE, and among them, only 16 specifically centered on women, highlighting the marginalization of both the educational modality and women themselves. Using the State of Knowledge methodology, the study aimed to comprehend the theoretical frameworks employed in these works, the gender and identity concepts addressed, and the contribution of the sociologist Norbert Elias to the subject. Through this analysis, convergences were observed among gender concepts, emphasizing how inequalities stemming from a sexist culture negatively impacted women's educational trajectories. On the other hand, the concept of identity was underexplored, revealing a gap in the understanding of the interpretation of these subjects. During the research, by mobilizing the concept of identity together with Elias' concept of individualization, it was possible to understand how a positive identity can contribute to women's return to education, not only modifying their self-esteem but also offering the possibility of a change in their functional role.